My rows and piles of coins - Mollel, Tololwa M. (Tololwa Marti); Lewis, Earl B. (New York : Clarion Books, 1999)
A Tanzanian boy saves his coins to buy a bicycle so that he can help his parents carry goods to market, but then he discovers that in spite of all he has saved, he still does not have enough money.
Notable/Best Books (A.L.A.).
School Library Journal starred.
Wilson's Children.
Book Links (A.L.A.), February 2001.
Booklist, August 1999.
Bulletin (Center for Children's books), October 1999.
Keywords: Bicycles -- Juvenile fiction; Money -- Juvenile fiction; Bicycles and bicycling -- Fiction; Money -- Fiction; Bicycles -- Fiction; Money -- Fiction; Tanzania -- Juvenile fiction; Tanzania -- Fiction; Tanzania -- Fiction